As bases teóricas da administração escolar no brasil: dos autores pioneiros na sua sistematização aos primeiros autores que elaboraram a crítica ao modelo clássico - Barboza, Jaqueline Lima (2024)
he theory of school administration in Brazil has undergone modifications over time. Thus, this thesis aims to analyze how the theory of Brazilian school administration has changed from the production of pioneering authors in its systematization to the first authors who elaborated a critique of this conception. The specific objectives are: a) to analyze the historical trajectory of school administration in Brazil from the colonial period to the 1990s; b) to list the works and main concepts of the theoretical production of the pioneering authors in the systematization of school administration, analyzing how this production was applied in Brazilian education; c) to understand the changes that occurred in school administration in the authors following the pioneers, examining the works and authors who were forerunners during the period known as the critical studies period. The research was conducted through bibliographic analysis, initially presenting the historical context that encompassed the theoretical production of the pioneering authors, as well as the first authors to elaborate a critique of this conception, and subsequently analyzing the most relevant works of authors from both perspectives. The first works to be published in Brazil on the subject under investigation date back to the post-1930s when industrialization and growing urbanization began in the country. As pioneers in the knowledge trajectory in the field of school administration in Brazil, we base our study on the following authors and their respective works: Antônio de Arruda Carneiro Leão with the work "Introduction to School Administration"; Anísio Spínola Teixeira with the work "Education for Democracy: Introduction to Educational Administration"; José Querino Ribeiro with the work titled "Essay on a Theory of School Administration"; and Manoel Bergstöm Lourenço Filho with the work "Organization and School Administration: Basic Course." After the 1980s, during Brazil's redemocratization period, the productions on school administration adopted a critical understanding of the theme, distancing themselves from the technical principles adopted by the pioneers to develop an administrative theory that better encompassed the specificities of Brazilian education. To this end, we consider the first authors and works to gain national prominence from this perspective, and they are: Miguel Gonzalez Arroyo with the article "Administration of Education, Power, and Participation"; Maria de Fátima Costa Félix with the work "School Administration: An Educational or Business Problem?"; and Vitor Henrique Paro with the work "School Administration: Critical Introduction." Our thesis is that the theory of school administration in Brazil underwent conceptual changes in the period after the 1980s, as from then on, scholars on the subject began new perspectives of investigation emphasizing Brazil's political and social characteristics through the application of critical analysis of a historical-sociological nature, and secondarily through the technical variables that were adopted by the pioneering authors.